Origin and significance of authigenic quartz and albite in lacustrine calcareous fine-grained sedimentary rocks. (September 2022) - Xiong, Zhouhai; Cao, Yingchang; Liang, Chao; Liu, Keyu; Wang, Guanmin; Zhu, Rui; Lei, Ping; Wang, Yanli
Abstract: Generally, researchers believe that authigenic quartz precipitates in acidic medium and authigenic albite precipitates in alkaline medium. However, the lacustrine carbonate-rich fine-grained sedimentary rocks in the upper fourth sub-member and the lower third sub-member (Es4 s –Es3 x ) of the Shahejie Formation in the Jiyang Depression were observed and it was found that authigenic microcrystalline quartz and albite generally develop together. Moreover, authigenic quartz and albite also develop with microcrystalline Fe-rich dolomite and calcite in clay laminae, while in carbonate laminae, they primarily develop with recrystallized calcite. In this study, thin-section, cathodoluminescence, field-emission scanning electron microscopy (FESEM), laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) and inclusion analyses were conducted to study authigenic minerals. The results show that authigenic quartz and albite are characterized by rich Ge in mudstone, and the material components mainly originate from the transformation of clay minerals and the dissolution of terrigenous feldspar debris. In limestone, they are characterized by poor Ge, and the material components primarily originate from the transformation of clay minerals. The paragrowth and intergrowth of authigenic quartz and albite primarily depend on the degree of supersaturation of the corresponding ion concentration under high temperature, high or ultrahigh pressure. During the early diagenetic stage, authigenic quartz and albite initially formed in a weakly alkaline environment; however, on entering the middle diagenetic period, authigenic quartz, albite, and sparry calcite formed in a weakly acidic environment, and the formation rate reached its peak. Our results elucidate the migration direction and enrichment law of shale oil in calcareous fine-grained sedimentary rocks through the genetic mechanism of authigenic quartzs and albites. Shale oil is generated from organic matter in the clay lamina, following which it migrates, accumulates, and preserves to the adjacent sparry calcite lamina under the joint driving effect of organic matter hydrocarbon generation overpressure and clay mineral dehydration overpressure. Highlights: The paragrowth and intergrowth of authigenic quartz and albite mainly depend on the degree of ionic supersaturation. Authigenic quartz and albite in mudstone primarily originate from clay minerals transformation and feldspar clasts dissolution. Authigenic quartz and albite in limestone primarily originate from the transformation of clay minerals. The origin mechanism of authigenic quartz and albite indicates the migration direction and enrichment mechanism of shale oil.